Antioxidative activity of tobacco leafprotein hydrolysates - Rao, Guohua (Array, 2007)
Discarded tobacco leaf protein hydrolysate (DTLPH) was prepared by enzymatic hydrolysis using papain and then separated using ultrafiltration (UF) membranes with molecular mass cut-off (MMCO) of 10, 5, 3 and 1 kDa. Four permeate fractions including 10-K, 5-K, 3-K and 1-K (the permeate fractions from 10, 5, 3 and 1 kDa) hydrolysate fractions were obtained. The 5-K hydrolysate fraction had high oxidation inhibilitory ratio (42.62 %), which was about twofold higher than the original hydrolysate and as high as that of vitamin E (α-tocopherol). The fractionated hydrolysates were superior to the original hydrolysate in the antioxidative activity tested. Moreover, these separated hydrolysates showed the enhanced functional property. The amino acid composition of 5-K hydrolysate was analyzed and the results show that the high antioxidative activity of 5-K hydrolysate was derived from high content of histidine, methionine, cystine and tryptophan